Implementasi Algoritma Squeezer dan Term Frequency Ranking dalam Pembangunan Sistem Rekomendasi Tempat Makan - Vincentius Wirawan; Seng Hansun; Hargyo Tri Nugroho I. (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2014)
Food is something that can not be separated from the life of every human being. Its variation makes a lot of people interested in tasting many types of food, even they have not known yet. The detail information of restaurants, especially their location could be a problem. So, the restaurants recommendation website is made to help them. The recommendations are given by the Squeezer algorithm using the user’s input as references. The accuracy of the given recommendations are determined from the amount and consistency of the user at the time of selecting the item. The Term Frequency Ranking is used as a searching feature to display the search results in ordered manner by their relevancy rank. Experiment result shows that the Term Frequency Ranking gives high value of Recall, 1, and 0.46 for the Precision value. Index Terms—Recommended System, Squeezer, Term Frequency Ranking, Website.